2017
DOI: 10.1139/cjpp-2016-0556
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of blockingN-methyl-d-aspartate receptors in male albino rats exposed to acute and repeated restraint stress

Abstract: Stress affects multiple organs in the body in addition to the brain including the liver. We aimed to assess the effects of blocking N-methyl-D-aspartate (NMDA) glutamate receptors by memantine on the liver in acute and repeated restraint stress. Forty two male albino rats divided into seven groups; control, Acute restraint stress (ARS), ARS+memantine, repeated restraint stress, repeated restraint +memantine and positive control groups. We measured serum iron, zinc, alanine transferase and Aspartame transferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 54 publications
2
6
0
2
Order By: Relevance
“…During I/R, the renal tubular epithelial cells experience disturbed cell polarity and cytoskeletal integrity, disrupted cell-cell and cell-matrix interactions, mitochondrial damage, and increased reactive oxygen species (ROS) synthesis [3][4][5]. Oxidative stress resulting from acute restraint stress has been determined to lead to hippocampal and hepatic damage [6]. Because oxidative stress can promote apoptosis, it also has the capacity to cause AKI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During I/R, the renal tubular epithelial cells experience disturbed cell polarity and cytoskeletal integrity, disrupted cell-cell and cell-matrix interactions, mitochondrial damage, and increased reactive oxygen species (ROS) synthesis [3][4][5]. Oxidative stress resulting from acute restraint stress has been determined to lead to hippocampal and hepatic damage [6]. Because oxidative stress can promote apoptosis, it also has the capacity to cause AKI.…”
Section: Introductionmentioning
confidence: 99%
“…Because oxidative stress can promote apoptosis, it also has the capacity to cause AKI. Indeed, a number of pathological kidney injuries have been attributed to apoptosis [6]. This finding has stimulated inquiries into the role of oxidative stress and apoptosis in the pathological process of I/Rinduced kidney injury.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the underlying molecular mechanism of acute stress-induced kidney injury is unclear. Previous studies have shown that injury of the liver [ 13 ] and hippocampus [ 14 ] caused by acute restraint stress is related to oxidative stress. As an inducer of apoptosis, oxidative stress can cause kidney damage [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Так, активация α 1 -и α 2 -адренорецепторов при остром стрессе вела к развитию умеренных дистрофических явлений в гепатоцитах [22], а также увеличению экспрессии и продукции ИЛ-6 этими клетками, ИЛ-1β -непаренхиматозными клетками печени [12], ФНОα, ИЛ-6, ТФР-1β -клетками Купфера [15], что создавало воспалительное микроокружение в тканях печени и вело к мобилизации и активации иммунных клеток. Активация нейтрофилов, клеток Купфера, а также миграция натуральных киллеров из селезенки наблюдалась в экспериментах моделирования острого стресса различной модальности [11,20,21].…”
Section: результаты исследования и их обсуждениеunclassified
“…Стресс является неизбежным следствием современного образа жизни, а также одним из факторов развития различного рода патологий, в том числе печени. Многочисленные исследования посвящены механизмам стресс-индуцированных повреждений, включающим усиление свободнорадикального окисления, развитие дистрофических изменений гепатоцитов [11,22], активацию апоптоза [22], что в конечном счете ведет к снижению функциональных возможностей паренхимы печени. Описана стрессогенная активация макрофагов, нейтрофилов [21] и клеток Купфера, создающая воспалительное микроокружение в тканях печени [20] и являющаяся важным индуцирующим фактором ее повреждения.…”
unclassified